Controlled release alginate-chitosan microspheres of tolmetin sodium prepared by internal gelation technique and characterized by response surface modeling - Mahmoud M. A. Elsayed (Universidade de São Paulo, 2021)
Tolmetin sodium (TS) is a powerful non-steroidal mitigating drug for the treatment of rheumatoid joint inflammation, osteoarthritis, and adolescent rheumatoid joint pain. In addition to its gastrointestinal (GIT) problems, TS has a short biological half-life (1 hr). In a trial to overcome these side effects and control the rate of (TS) release, chitosan coated alginate microspheres are recommended. A Box-Behnken experimental design was employed to produce controlled release microspheres of TS in the sodium alginate and chitosan copolymers (Alg-Ch) by emulsification internal gelation methodology. The effect of critical formulation variables namely, drug to polymer ratio (D:P ratio), speed of rotation and span 80% on drug encapsulation efficiency (% EE), drug release at the end of 2 hours (Rel2) and drug release at the end of 8 hours (Rel8) were analyzed using response surface modeling. The parameters were assessed using the F test and mathematical models containing only the significant terms were generated for each parameter using multiple linear regression analysis. The produced microspheres were spherical in shape with extensive pores at D:P ratio 1:1 and small pores at a drug to polymer ratio (D:P ratio) 1:3. Differential scanning calorimetry (DSC) affirmed the steady character of TS in microspheres and revealed their crystalline form. All formulation variables examined exerted a significant influence on the drug release, whereas the speed emerged as a lone factor significantly influencing % EE. Increasing the D: P ratio decreases the release of the drug after two and 8 hours. The increase in speed results in an increase in drug release after two and eight hours. The drug release from the microspheres followed zero order kinetics. TS Alg-Ch microspheres exhibited a significant anti-inflammatory effect on incited rat paw edema after eight hours. These results revealed that the internal gelation technique is a promising method to control TS release and eradicate GIT side effects using Alg-Ch copolymers.